Bioeconomics as a component of the "green" economy (Journal of Economic Research & Business Administration, 2022)
The objective inconsistency of the traditional linear model of the economy forces us to look for neweconomic models that meet modern requirements of conscious consumption, when economic development,environmental well-being and the quality of life of people, including future generations, areof equal importance. The idea of sustainable development, which emerged in the 80s of the last century,served as the basis for the emergence and development of new economic concepts, including the«green» economy and bioeconomics.The aim of the research is to systematize the accumulated knowledge about the «green» economyand bioeconomics, as well as to establish the nature of their relationship. The article analyzes the stagesof the formation of bioeconomics as a concept, gives a general idea of the institutional context of eachof the time periods, pays special attention to the transformation of the arguments for popularizing theconcept of bioeconomics, and offers a criterion for a more accurate understanding of what belongs tothe «green» economy and what does not.The study examined the internal structure and patterns of development of the concept of sustainabledevelopment. A comparative historical analysis of the evolution of the concept of bioeconomics, includingthe study of normative legal acts devoted to the development of the «green» economy, revealed thecause-and-effect relationships regarding its popularization.Despite the position of the regional leader in all that concerns the ratification of initiatives relatedto sustainable growth and the development of the «green» economy, bioeconomics in Kazakhstan isgiven little attention. The main strategic document regulating the transition of Kazakhstan to the «green» economy, in addition to the «green» initiatives, has incorporated elements of bioeconomics and closedloopeconomy, which does not allow to fully realize the domestic potential in achieving sustainabledevelopment.Key words: «green» economy, bioeconomics, sustainable development.